Analysis of crystalline and solution states of ligand‐free spermidine N‐acetyltransferase (SpeG) from Escherichia coli. Issue 6 (18th June 2019) - Filippova, Ekaterina V.; Weigand, Steven; Kiryukhina, Olga; Wolfe, Alan J.; Anderson, Wayne F.
Abstract : The structure of ligand‐free spermidine N ‐acetyltransferase (SpeG) from Escherichia coli is described. Structural analysis was performed using X‐ray crystallography and was combined with SEC‐MALS, SAXS and negative‐staining EM for characterization of the solution structure. In solution, SpeG from E. coli exhibits an oligomeric composition that is distinct from that of its homolog from Vibrio cholerae . Abstract : Spermidine N ‐acetyltransferase (SpeG) transfers an acetyl group from acetyl‐coenzyme A to an N‐terminal amino group of intracellular spermidine. This acetylation inactivates spermidine, reducing the polyamine toxicity that tends to occur under certain chemical and physical stresses. The structure of the SpeG protein from Vibrio cholerae has been characterized: while the monomer possesses a structural fold similar to those of other Gcn5‐related N ‐acetyltransferase superfamily members, its dodecameric structure remains exceptional. In this paper, structural analyses of SpeG isolated from Escherichia coli are described. Like V. cholerae SpeG, E. coli SpeG forms dodecamers, as revealed by two crystal structures of the ligand‐free E. coli SpeG dodecamer determined at 1.75 and 2.9 Å resolution. Although both V. cholerae SpeG and E. coli SpeG can adopt an asymmetric open dodecameric state, solution analysis showed that the oligomeric composition of ligand‐free E. coli SpeG differs from that of ligand‐free V. cholerae SpeG. Based on these data, it is proposed that the equilibrium balance of SpeG oligomers in the absence of ligands differs from one species to another and thus might be important for SpeG function.